EVALUATING THE IMPLEMENTATION OF JEMBER REGENCY SPATIAL PLANNING REGULATION NO. 1 OF 2015 IN GEOMORPHOLOGICAL CONSERVATION OF HUMMOCKS (GUMUK) - Emanuel Grace Manek; Kurnia Dewi Mulyani; Utari Retno Sulistyo Rini (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
Jember Regency in East Java, Indonesia, possesses a distinctive geomorphological landscape dominated by small, rounded hills locally referred to as gumuk. These landforms play a crucial ecological role as natural wind barriers, regulators of regional groundwater systems, and providers of habitats that support local biodiversity. Nevertheless, the rising demand for Category C mining resources has accelerated the exploitation of gumuk, posing serious threats to environmental sustainability and eroding Jember’s historical identity as the “City of a Thousand Gumuk.” This study employs a qualitative literature review to analyze the relationship between local spatial policies and conservation efforts, with particular attention to Jember Regional Regulation No. 1 of 2015 on Spatial Planning, which designates gumuk as a Geological Protected Area. The examination of historical disaster data, spatial patterns of extreme winds, and land-use transformation indicates an increasing susceptibility of Jember Regency to natural hazards, especially strong winds and flooding. The degradation and removal of gumuk due to mining activities reduce natural protective functions, heighten disaster risks, and disturb groundwater stability. Although regulatory frameworks exist, weak enforcement has resulted in persistent illegal mining, highlighting a significant disconnect between policy formulation and implementation. To mitigate these issues, the study recommends systematic mapping and zoning of gumuk based on scientific criteria, alongside strengthening public awareness and community involvement. Sustainable utilization through eco-tourism and youth-based entrepreneurship is also encouraged. In alignment with Law No. 32 of 2009 and the Sustainable Development Goals (SDGs 11, 13, and 15), this paper concludes that conserving gumuk is vital for ecological resilience and the preservation of Jember’s regional identity.